Issues in internet adoption: a study among Sri Lankan rural communities - Galagedarage Thushari Madhubhashini,; Ali Salman,; Wan Amizah Wan Mahmud,; Fauziah Ahmad, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
Internet user percentage in Sri Lanka has lingered at a mere 13.1% in 2011 according to an Annual report by Department of Census and Statistics in Sri Lanka. The aim of this paper is to identify the issues hindering rural internet adoption in Sri Lanka. This paper will report results of descriptive statistics, mean score for the dependent variable and independent variables and results of correlation analysis regarding the relationship between internet adoption and infrastructure facilities, adopter characteristics of rural communities, technology characteristics and affordability. A survey using questionnaire was used to obtain data from 400 respondents in Bibile, Monaragala district. The results show that internet adoption among the rural communities was low due to lack of infrastructure facilities, problem of affordability and low in computer skills. The mean scores for affordability, infrastructure facilities and computer skills, have high effect with internet adoption. The variables, viz. adopter characteristics (needs, relevancy, attitudes, English language skills), technology characteristics (ease of use, perceived benefits) have average effect with internet adoption. From the correlation results adopter characteristics and technology characteristics have strong significant positive relationships with internet adoption. There is a strong significant negative relationship between internet adoption and infrastructure facilities, computer skills and affordability. The government or non-government organizations should introduce ICT policies; improve infrastructure facilities, socioeconomic situation and computer skills in order to increase internet adoption among rural communities in Sri Lanka. Therefore, this study suggests that efforts must be made to address the issues hampering the adoption of the internet among the rural communities.